2020
DOI: 10.1016/j.jcmgh.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenetic Mechanisms in Diverticular Disease of the Colon

Abstract: This article reviews epidemiological evidence of heritability and putative mechanisms in diverticular disease, with greatest attention to 3 recent studies of genetic associations with diverticular disease based on genome-wide or whole-genome sequencing studies in large patient cohorts. We provide an analysis of the biological plausibility of the significant associations with gene variants reported and highlight the relevance of ANO1, CPI-17 (aka PPP1R14A), COLQ6, COL6A1, CALCB or CALCA, COL6A1, ARHGAP15, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 146 publications
(112 reference statements)
2
49
0
9
Order By: Relevance
“…This individual's diverticula were mostly localized to the ascending and transverse colon, which is consistent with diverticulosis in Asian and African populations [4,5]. Diverticular disease has an estimated genetic contribution of 40% to 53% [10]. The presence of extensive diverticula in this individual could be linked to a genetic predisposition for diverticulosis exacerbated by additional lifestyle risk factors [10].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This individual's diverticula were mostly localized to the ascending and transverse colon, which is consistent with diverticulosis in Asian and African populations [4,5]. Diverticular disease has an estimated genetic contribution of 40% to 53% [10]. The presence of extensive diverticula in this individual could be linked to a genetic predisposition for diverticulosis exacerbated by additional lifestyle risk factors [10].…”
Section: Discussionsupporting
confidence: 69%
“…Diverticular disease has an estimated genetic contribution of 40% to 53% [10]. The presence of extensive diverticula in this individual could be linked to a genetic predisposition for diverticulosis exacerbated by additional lifestyle risk factors [10]. Specifically, collagen cross-linking defects are speculated to play a role in diverticulosis cases with high diverticula quantity [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic connective tissue disorders like Ehlers-Danlos and Marfans syndrome have been linked to the development of diverticulosis in young age [34,35]. Some studies indicated that genes involved in immunity, extracellular matrix, cell adhesion, membrane transport and intestinal motility may be related to diverticular disease [36][37][38]. However, the exact mechanisms remain to be shown.…”
Section: What Are the Risk Factors For Diverticulosis Diverticulitismentioning
confidence: 99%